Methodologies for physical geography teacthing - Louzada, Camila de Oliveira; Frota Filho, Armando Brito (Geosaberes; Vol 8 No 14 (2017): Jan - Apr, 2017)
One of the main difficulties encountered by students from elementary school (1st to 9th grader) and high school (1st to 3rd grade) in educational institutions in Brazil is the assimilation of Physical Geography's content presented in the Geography's textbooks. Among the methodologies to be presented, the first is the Realias that consist of present set of objects representing a content, providing the association between this object with the subject to study, another methodology and teaching resource is the Terrarium, which consists of full reproduction of a ecosystems in miniaturewithin objects. And as a third alternative, which involves the relationship between theory and praxis is to use the "field work" due to their importance to the visualization of environmental dynamics in situ. Another method is the "Environmental Studies", which allows the student to relate the contents studied with the phenomena related to the daily life. As a fifth alternative will present the methodology of Mental Maps, which are representations through drawings, the perception of the places lived by the interviewees. In order to provide a set of methodological tools to assist teachers and students in teaching and learning of physical geography content.
Keywords: Geografia Física; Metodologias; Ensino-Aprendizagem